PERLINDUNGAN MASYARAKAT HUKUM ADAT DI KABUPATEN LUWU TIMUR - Haedar Djidar; Andi Jaka Hendra (Journal Publicuho, 2024)
This research aims to find out and analyze the role of the East Luwu district government towards customary law communities. and To find out what the obstacles are in implementing the protection of customary law communities in East Luwu district. This type of research was carried out using the Normative-Empirical method. The results of the research show that East Luwu Regency, in recognizing and protecting its customary law communities, is by enacting Regional Regulation Number 1 of 2022 concerning Recognition and Protection of Customary Law Communities, where the regulation aims to provide legal certainty regarding the position and existence of customary law communities. Obstacles in the recognition and protection of customary law communities are related to legal factors where there are no more specific regulations governing the protection and recognition of customary law communities.